The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1111/j.1699-0463.1997.tb05104.x
|View full text |Cite
|
Sign up to set email alerts
|

Revascularisation of human parathyroid tissue transplanted to athymic mice

Abstract: The revascularisation process of transplanted human normal, hyperplastic and adenomatous parathyroid tissue was analysed at 2 and 4 days and 1, 2, 4, 7 and 12 weeks after transplantation to athymic mice. The transplants were examined by light and electron microscopy, immunohistochemistry and autoradiography. Vessels were detected by monoclonal antibodies specific for mouse and human endothelial cells. Immunohistochemistry demonstrated ingrowth of vessels from the host into the transplant and at one week numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Fresh human PT tissue has proven functional when transplanted subcutaneously into athymic 238 mice (3,4). We have in these previous studies found a high take ratio, preserved morphology and a high area fraction of viable xenotransplanted normal, hyperplastic and adenomatous PT tissue, and we have further observed that adenomatous PT tissue had the highest proliferation rate and that transplanted PT tissue secretes human PTH (3).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Fresh human PT tissue has proven functional when transplanted subcutaneously into athymic 238 mice (3,4). We have in these previous studies found a high take ratio, preserved morphology and a high area fraction of viable xenotransplanted normal, hyperplastic and adenomatous PT tissue, and we have further observed that adenomatous PT tissue had the highest proliferation rate and that transplanted PT tissue secretes human PTH (3).…”
Section: Discussionsupporting
confidence: 51%
“…It was, however, also found that the transplants showed varying degrees of cell disintegration (3). Capillary sprouting into the periphery of the transplants was observed during the first week, but only at 4 to 7 weeks were mature capillaries noticed (4). Despite this, measurable amounts of PTH from the transplants were observed at one week after transplantation.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…These findings indicate that it is even mandatory to simultaneously assay angiogenesis and endocrine function to really address transplant-induced, and thus specific, angiogenic activity. Ander et al (8) studied in detail early angiogenesis of human parathyroid tissue transplanted into nude mice. With species-specific antibodies, mouse-human microvessel chimeras were histologically detectable in the first week.…”
Section: Angiogenesis Of Parathyroid Transplantsmentioning
confidence: 99%
“…Likewise, parathyroid tissue can induce angiogenesis in vitro (6) and in vivo (7). Angiogenic activity was observed during the first week after transplantation (8). Moreover, it was shown that transplanted parathyroid tissue is capable of spontaneous reinnervation along newly built blood vessels after 1 week (9).…”
mentioning
confidence: 96%